Pediatric unicystic cystic partially differentiated nephroblastoma: The first case report - Chao, Liu; Lei, Zhang; Xiang, Li; Qi, Zhou (Frontiers in Pediatrics, 2022)
Cystic partially differentiated nephroblastoma (CPDN) has been reported to date, all of which present as polycystic renal tumor. It is a special pathological type of nephroblastoma. Here we report the first case of unicystic CPDN in children. The patient was diagnosed as simple renal cyst and underwent laparoscopic decortication. The naive nephron was found in the pathological section and the diagnosis of CPDN was confirmed. The patient then underwent radical nephrectomy and six cycles of postoperative chemotherapy. There was no recurrence or metastasis after 2 years of follow-up. Pediatric CPDN presenting as an unicystic renal tumor poses a new challenge to the diagnosis, differential diagnosis and treatment of unicystic renal tumor.